Amphiphilic graft copolymers with ethyl cellulose backbone: Synthesis, self-assembly and tunable temperature–CO2 response. (20th January 2016) - Yuan, Weizhong; Zou, Hui; Shen, Jin
Highlights: Amphiphilic ethyl cellulose-based brush copolymers were synthesized by ATRP. These brush copolymers can self-assemble to micelles. The micelles presented switchable temperature–CO2 dually responsive properties. The micelles could achieve the control release of DOX. Abstract: Amphiphilic ethyl cellulose- graft -poly(N, N-dimethylaminoethyl methacrylate) (EC- g -PDMAEMA) and ethyl cellulose- graft -poly(2-(2-methoxyethoxy)ethyl methacrylate- co -N, N-dimethylaminoethyl methacrylate) (EC- g -P(MEO2 MA- co -DMAEMA)) graft copolymers were easily synthesized by atom transfer radical polymerization (ATRP). The micelles self-assembled from the copolymer presented switchable temperature–CO2 dually responsive properties. The value of lower critical solution temperature (LCST) for the copolymer micelle solutions could be adjusted by CO2 /Ar. Moreover, due to the alteration of the ratio of DMAEMA to MEO2 MA, the LCST values of the micelle solutions decreased with the increase of MEO2 MA in copolymer. The temperature–CO2 dually responsive properties of the copolymer were reversible and could be accomplished through altering the temperature and bubbling CO2 /Ar. The hydrodynamic radius ( R h ) of the copolymer micelles was also influenced by the ratio of DMAEMA to MEO2 MA and the stimuli of temperature and CO2 /Ar. As a drug release system, the copolymer micelles could achieve the control release of doxorubicin (DOX) by changing the temperature and alternatively bubbling CO2 /Ar.